The Properties of Treating Waste Printed Circuit Boards by Ionic Liquids - DONG Jing-hao; YAN Wen-hui; ZHANG Ting; GUO Heng-bo; SONG Liu-yu (Journal of Harbin University of Science and Technology)
Improper treatment about waste printed circuit boards (WPCBs) can cause serious environmental pollution and resources waste. In this study, 1-butyl3-methyl-imidazolium hydrogen sulfate (［Bmim］HSO4) was synthesized through two-step reaction Separation properties of WPCBs treated by ［Bmim］HSO4 was investigated. The influence of treatment temperature, reaction time and particle size of WPCBs on dismantlement of WPCBs were focused. Experimental results indicated that WPCBs can be separated efficiently and non-polluted. The maximum dissolution of brominated epoxy resin (BER) in WPCBs occurred by controlling the system temperature, heating time, the size of WPCBs at 270℃, 20±2min and 2×2cm2, respectively. The used ［Bmim］HSO4 can be recycled. This study offers an effectively way to recycle WPCBs and prevent the environmental pollution of WPCBs.